Highly compact surface micromachined metamaterial circuits using multilayers of low-loss Benzocyclobutene for microwave and millimeter wave applications (2012)
This work explores the implementation of highly compact three dimensional (3D) integrable metamaterial based transmission lines on a low resistivity CMOS grade silicon substrate for microwave and millimeter wave applications. The composite right-left handed (CRLH) architecture is able to be integrated with an integrated circuit (IC) using a multilayer surface micromachined fabrication process as a post-CMOS process. The fabrication process employs the negative tone photo sensitive Benzocyclobutene (BCB) as a low-loss dielectric interlayer material allowing packaging compatible high performance RF circuits. Since the low temperature and multilayer fabrication is compatible with CMOS/MEMS processes, it allows the batch fabrication of multiple devices and the easy implementation of 3D vertical interconnects. The design, modeling, fabrication and on-wafer characterization are presented for 50 Ω compact multilayer finite ground coplanar waveguide (FGC) CRLH unit cells and transmission lines for broadband and multiband operation at Ku and Ka frequencies of 14 GHz and 35 GHz, respectively. Also, the comparison between the simulation and measurement results up to 40 GHz on the aforementioned 3D electromagnetic structures is provided. The left handed capacitance and inductance components of the CRLH structures are implemented with photolithographically defined Metal-Insulator-Metal (MIM) capacitors and BCB embedded meander inductors, respectively, which allows the fabrication of very compact CRLH devices. The fabricated dual band unit cell features a size of λ 0/30 at 14 GHz and an insertion loss of less than 2dB within the passband. © 2012 IEEE.